Crystalline BeO Grown on 4H-SiC via Atomic Layer Deposition: Band Alignment and Interface Defects - Lee, Seung Min; Jang, Yoonseo; Jung, Jongho; Yum, Jung Hwan; Larsen, Eric S.; Lee, Sang Yeon; Seo, Hyungtak; Bielawski, Christopher W.; Lee, Hi Deok; Oh, Jungwoo (ACS Applied Electronic Materials, 2019)
A crystalline beryllium oxide (BeO) film was grown on 4H-silicon carbide (4H-SiC) via thermal atomic layer deposition (ALD). Diethylberyllium and water were used as key precursors. The growth rate of BeO corresponded to 0.8 Å/cycle over the temperature range of 150-200 °C. Transmission electron microscopy and X-ray diffraction of BeO/4H-SiC demonstrated that wurtzite BeO (0002) was grown on 4H-SiC (0001) substrate. The average crystallite sizes of BeO were 15-16 nm, and the compressive strain was applied to the BeO film in the out-of-plane direction. The band alignment and interface defects of BeO/4H-SiC were determined by using internal photoemission spectroscopy (IPE), ultraviolet photoelectron spectroscopy (UPS), and reflection electron energy loss spectroscopy (REELS). The conduction band offset (CBO), valence band offset (VBO), and energy bandgap of 4H-SiC and BeO corresponded to 2.28 ± 0.1 eV, 2.53 ± 0.01 eV, 3.16 ± 0.1 eV, and 8.3 ± 0.05 eV, respectively. The calculated bandgap (7.97 eV) of a thin BeO film was obtained from the sum of CBO (2.28 eV), VBO (2.53 eV), and the SiC bandgap (3.16 eV). The difference between the calculated (7.97 eV) and REELS (8.3 eV) bandgaps of BeO film is due to the error bars between the analysis methods. Interface defect levels, as determined via IPE analysis, corresponded to 3.53 ± 0.1 eV (graphitic carbon) and 4.46 ± 0.1 eV (π-bonded carbon) and were formed during the ohmic annealing process.
Keywords: 4H silicon carbide; Compressive strain; Conduction band offset; Graphitic carbons; Internal photoemission spectroscopies; Out-of-plane direction; Reflection electron energy loss spectroscopies; Valence band offsets; band alignment; beryllium oxide (BeO); internal photoemission spectroscopy (IPE); reflection electron energy loss spectroscopy (REELS); silicon carbide (SiC); ultraviolet photoelectron spectroscopy (UPS)